CHALLENGES IN TRANSLATING IDIOMATIC EXPRESSIONS RELATED TO CUSTOMS AND RITUAL TERMINOLOGY IN SIMULTATEOUS INTERPRETATION - Laylo KOMILJANOVA (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA’LIMNING INNOVATSION YO’NALISHLARI, 2025)
Simultaneous interpretation poses unique challenges, especially when it involves culturally bound idiomatic expressions related to customs and rituals. These expressions often lack direct equivalents in the target language, creating a high risk of misinterpretation or cultural loss. This paper examines the specific difficulties that interpreters encounter when translating idiomatic expressions embedded in cultural traditions and ceremonial discourse. The analysis draws on theoretical frameworks from translation studies and practical observations in the field, ultimately offering strategies for managing cultural specificity in real-time interpretation settings.